Study of a mixture of soil and brazilian bentonite using a protocol for clay characterization for near-surface radioactive waste repository - Samara Alves Barroso; Clédola Cássia Oliveira de Tello (Brazilian Journal of Radiation Sciences, 2021)
Aiming to implement the Brazilian repository for disposal of low and intermediate level of radioactive wastes, the “Project RBMN” is being coordinated by CNEN. The repository is made of multiple barriers in order to prevent or retain the migration of radionuclides throughout these paths to the environment. Clays are used as backfill and coverage layers, which are the repository natural barriers. Recently, in Nuclear Technology Development Center (CDTN) a protocol for clay characterization was elaborated, and it was used the Brazilian bentonite as a reference. In this protocol are established some physical and chemical tests and their reference values that are essential for the characterization of materials to be used as backfill and coverage layers in the surface repository. This research intended to evaluate the applicability of this protocol to characterize soil without and with bentonite. The bentonite content added to the soil was 30%. The results were compared with the reference values of the protocol and literature for materials with similar mineralogical features. The results showed an increase of the specific surface and of the cation exchange capacity, as the result of the bentonite addition. The hydraulic conductivity is significant decreased by the addition of bentonite.